THE ROLE OF SOCIAL MEDIA AND GENDER-BASED VIOLENCE: HOW PSYCHOLOGY CAN CONTRIBUTE TO ADDRESSING THESE PRACTICES - Santos, Allyson Yann Batista; Messias, Juliana Penha; de Matos Neto, Danubio Freire Gomes; da Silveira, Francisca Morais (Seven Editora, 2026)
Gender-based violence constitutes a structural phenomenon sustained by historical, cultural, and political inequalities that place women in situations of vulnerability. Based on a literature review, this study investigated the relationship between violence against women, media discourses, and social media dynamics, also considering the contributions of Psychology in addressing this context. Recent national data show that millions of women remain exposed to domestic violence and various forms of aggression, which now also manifest in the virtual environment. The analysis of media production reveals that normalization, victim-blaming, and revictimization continue to be present in journalistic coverage and digital content, reinforcing gender stereotypes and perpetuating discriminatory practices. Psychology, guided by ethical-political principles and the recognition of intersectionalities, plays a central role in prevention, support, and the promotion of women’s autonomy, working in articulation with the Protection Network. Although the literature demonstrates advances, a scarcity of studies integrating gender-based violence, social media, and psychological impacts was observed, indicating the need to expand research on how the digital environment influences social perceptions and subjective processes involved in violence against women. DOI: https://doi.org/10.56238/sevened2026.008-053